PENANAMAN AQIDAH AHLUSSUNNAH WAL JAMA’AH MELALUI KEGIATAN UBUDIYAH DI SEKOLAH MENENGAH ATAS ISLAM ALMAARIF SINGOSARI MALANG - R. Faizal Hamdi Humidat; Muhammad Afifulloh; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The world of education has always been a place to guide and shape students into individuals who have the ability to think and the ability to do good deeds.Therefore, the existence of educational institutions greatly influences the development of students. With this, considering the development of students' knowledge of the aqidah that exists in Islam, if an educational institution is needed as an intermediary to provide knowledge to students, thus educational institutions are required to provide understanding to students so that they have the correct understanding of Aswaja's aqidah in order not to be affected. to the schools that have been condemned out of the true Aswaja teachings. So that the Almaarif Islamic High School educational institution has an Ubudiyah program of activities that can provide students with an understanding of good aqidah aswaja so that students avoid understanding aqidah that deviates from the true aqidah and also so that students become devout Muslim individuals.